Hubungan Aktivitas Olahraga Dengan Tingkat Kebugaran Sebagai Upaya Pencegahan Mandiri Dalam Menghadapi COVID-19 Desa Somagede Kecamatan Somagede - Setianingsih, Endhah; Susilo, Rakhmat (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: To figure out the correlation between sports activities and fitness levels as a personal prevention effort in facing Covid-19 in Somagede village, Somagede sub-district. Methods: The study used a quantitative research method with a correlation and cross-sectional research design. The samples were collected using a random sampling technique with 91 respondents. Results: The results showed that there were 51 respondents (56%) whose age was between 17-25 years with an average of 25.56 years. The gender was mostly female that consisted of 52 respondents (57.1%). There were 42 respondents (46.2%) who worked as private employees. The result of the chi-square test obtained a p-value of 0.005 which was smaller than a = 0.05. Conclusion: There was a correlation between sports activities and fitness level as a personal prevention effort in facing Covid-19 in Somagede village, Somagede sub-district. It is expected that the community will maintain its level of physical fitness in the midst of this Covid-19 pandemic by carrying out adequate sports activities in accordance with the health protocol.